Exsudatos de plantas: um estudo de revisão e efeito anti-helmíntico sobre o nematoide Haemonchus contortus - LICÁ, Irlla Correia Lima (2018)
Gastrointestinal nematode infection is considered the main sanitary problem of small ruminants Haemonchus contortus is the most prevalent endoparasite and pathogenicity. The indiscriminate and continued use of anthelmintic products has selected resistant populations of the parasites to these products. Products of natural origin in particular of plants have been considered as a potential alternative in the control of gastrointestinal parasites. However, studies on the identification of proteins obtained from exudates of plant seeds are rare. Thus, the present work was divided into two chapters in order to expand prospective studies on the search for new bioactive compounds derived from plant exudates. In chapter 1, we provide through a review, an overview on the exudates released by the biological properties of plants, their and the presence of several compounds, obtained and analyzed by different procedures. In Chapter 2, the objective was to identify proteins from the protein exudates of Mimosa caesalpiniaefolia, Leucaena leucocephala, Acacia mangium and Stylosanthes capitata seeds, as well as evaluate their anthelmintic action on the gastrointestinal nematode H. contortus. After sanitization, the seeds were soaked in sodium acetate buffer (0.1M, pH 5.0) for 24h at 10 °C. Proteins present in the exudates were obtained by fractionation with ammonium sulphate (0-90%). After precipitation, the exudates were incubated for 4 h at 10 °C and the proteins recovered by centrifugation (12,000 x g, 4°C 30 min). The supernatant was discarded and the pellet was resuspended in 0.1 M sodium acetate buffer, pH 5.0 and dialyzed against water (cut off: 2 kDa), lyophilized and stored (-20 oC). The protein content in the exudates was evaluated, as well as the inhibitory effect of egg hatching (EHA) and larval exsheathment inhibition assay (LEIA) of H. contortus. There was obtained 0.49; 0.06; 0.10; and 0.11 micrograms of proteins exuded per gram of seeds, respectively, in M. caesalpiniaefolia; L. leucocephala; A. mangium and S. capitata. Although the exudates did not inhibit egg hatching, they inhibited the drawing of H. contortus larvae at effective concentrations, EC50, ranging from 0.26 to 0.61 mg/mL. Exudates of L. leucocephala and S. capitata were more effective on inhibition of larvae larvae (EC50 0.26 and 0.40 mg/mL, respectively). According to data obtained by mass spectrometry of the exudates, several proteins were detected, among them protease, protease inhibitor, chitinase and lectin. Thus, through this study on seed exudates on H. contortus, we conclude that they present several proteins related to plant defense and that may be related to larval exsheathment inhibition assay nematode, characterizing itself as a potential alternative to the control of this parasite